Effects of climate change on mast‐flowering cues in a clonal montane herb, Veratrum tenuipetalum (Melanthiaceae)1. Issue 3 (1st March 2013) - Iler, Amy M.; Inouye, David W.
Abstract : Premise of the study: Climate change threatens to alter the timing and magnitude of abiotic cues that synchronize mast flowering, such as temperature and precipitation. Climate change may therefore alter the frequency of masting, in turn affecting species in the community that use pulsed resources. Methods: We used 29‐yr (1984–2012) records of climate and flowering to investigate proximate flowering cues for the clonal, mast‐flowering herb Veratrum tenuipetalum . Because clonal reproduction is tied to flowering in Veratrum, we used a parallel record of ramet abundance to examine the effects of masting on long‐term ramet abundance. Key results: Cool summer temperatures 2 years before flowering were associated with a higher percentage of flowering in Veratrum populations, consistent with its life history. Ramet abundance increased by 9.5% ± 5.6% on average following mast years compared to an average loss of 0.73% ± 1.1% in nonmast years, and ramet abundance increased over the time frame of our records. Conclusions: Ramet abundance has increased over the time frame of our records mainly because of clonal reproduction in masting years. If summer temperatures continue to increase at our site and Veratrum does not alter its climate thresholds, we predict that masting will become less frequent in this species, with consequent reduction in opportunities for both sexual and clonal reproduction.